Nurses in municipal care of the elderly act as pharmacovigilant intermediaries: a qualitative study of medication management. (2nd January 2016) - Johansson-Pajala, Rose-Marie; Jorsäter Blomgren, Kerstin; Bastholm-Rahmner, Pia; Fastbom, Johan; Martin, Lene
Abstract: Objective: To explore registered nurses' experience of medication management in municipal care of the elderly in Sweden, with a focus on their pharmacovigilant activities.Design: A qualitative approach using focus-group discussions was chosen in order to provide in-depth information. Data were analysed by qualitative content analysis.Setting: Five focus groups in five different long-term care settings in two regions in Sweden.Subject: A total of 21 registered nurses (RNs), four men and 17 women, aged 27–65 years, with 4–34 years of nursing experience.Results: The findings reveal that RNs in municipal long-term care settings can be regarded as "vigilant intermediaries" in the patients' drug treatments. They continuously control the work of staff and physicians and mediate between them, and also compensate for existing shortcomings, both organizational and in the work of health care professionals. RNs depend on other health care professionals to be able to monitor drug treatments and ensure medication safety. They assume expanded responsibilities, sometimes exceeding their formal competence, and try to cover for deficiencies in competence, experience, accessibility, and responsibility-taking.Conclusion: The RNs play a central but also complex role as "vigilant intermediaries" in the medication monitoring process, including the issue of responsibility. Improving RNs' possibility to monitor their patients' drug treatments would enable them to prevent adverse drug events in their daily practice. New strategies are justified to facilitate RNs' pharmacovigilant activities. Key points: This study contributes to the understanding of registered nurses' (RNs') role in medication management in municipal care of the elderly (i.e. detecting, assessing, and preventing adverse drug events or any drug-related problems). RNs can be considered to be "vigilant intermediaries" in elderly patients' drug treatments, working at a distance from staff, physicians, and patients. RNs occasionally take on responsibilities that exceed their formal competence, with the patients' best interests in mind. In order to prevent adverse drug events in municipal care of the elderly, new strategies are justified to facilitate RNs' pharmacovigilant activities.